Ethylene is involved in brassinosteroids induced alternative respiratory pathway in cucumber (Cucumis sativus L.) seedlings response to abiotic stress - Wei, Lijie; Deng, Xing-Guang; Zhu, Tong; Zheng, Ting; Li, Peng-Xu; Wu, Jun-Qiang; Zhang, Da-Wei; Lin, Hong-Hui (Frontiers in Plant Science, 2015)
Effects of brassinosteroids (BRs) on cucumber (Cucumis sativus L.) abiotic stresses resistance to salt, polyethylene glycol (PEG), cold and the potential mechanisms were investigated in this work. Previous reports have indicated that BRs can induce ethylene production and enhance alternative oxidase (AOX) pathway. The mechanisms whether ethylene is involved as a signal molecule which connected BR with AOX in regulating stress tolerance are still unknown. Here, we found that pretreatment with 1 µM brassinolide (BL, the most active BRs) relieved stress-caused oxidative damage in cucumber seedlings and clearly enhanced the capacity of AOX and the ethylene biosynthesis. Furthermore, transcription level of ethylene signaling biosynthesis genes including ripening-related ACC synthase1 (CSACS1), ripening-related ACC synthase2 (CSACS2), ripening-related ACC synthase3 (CSACS3), 1-aminocyclopropane-1-carboxylate oxidase1 (CSACO1), 1-aminocyclopropane-1-carboxylate oxidase2 (CSACO2) and CSAOX were increased after BL treatment. Importantly, the application of the salicylhydroxamic acid (SHAM, AOX inhibitor) and ethylene biosynthesis inhibitor aminooxyacetic acid (AOA) decreased plant resistance to environmental stress by blocking BRs-induced alternative respiration. Taken together, our results demonstrated that ethylene was involved in BRs-induced AOX activity which played important roles in abiotic stresses tolerance in cucumber seedlings.